Pengenalan Permainan Tradisional Bali Dolanan Bagi Anak Usia Dini - Arini, Ni Putu Sri; Gede Anadhi, I Made; Komang Sindu Putra, Ida Bagus (UIR PRESS, 2024)
The aim of this research is to reintroduce the traditional Balinese game dolanan, whose existence needs to be maintained so that it is not eroded by the era that is starting to be touched by modern culture. The type of research used is literature review research with a focus on the traditional Balinese game